Abstract For Thoracolumbar Trauma - Shankar Gopinath (Indoscholar, 2018)
In both adult and pediatric populations, thoracolumbar trauma accounts for a large portion of traumatic injuries. There is a wide spectrum of injury types, including compression fractures, burst fractures, fracturedislocations, and more. The traditional treatment for many of these has been instrumented stabilization by an “open” approach. However, as minimally invasive techniques have been developed for degenerative disorders, there has been considerable interest in bringing the same benefits of decreased blood loss, improved wound exposure, and potentially decreased operative time to the trauma population. Further, “minimally invasive” is a broad category, encompassing percutaneous pedicle screw fixation, endoscopic/thoracoscopic approaches, and anterior column reconstruction. A few authors have put forward some algorithms of selecting appropriate patients for MIS techniques. However, the majority of published data has been limited to small case series with very heterogeneous pathologies. Further studies are needed to assess minimally invasive surgery for thoracolumbar spine trauma, with respect to short- and long-term clinical outcome, fusion rates/radiographic outcome, and cost-effectiveness.